THE DETERMINATION OF RATIONAL PARAMETERS OF THE NOMINAL MODE OF THE TRACTION MEANS OF RAIL TRANSPORT - Getman, H. K.; Mykhaylenko, Yu. V.; Arpul, S. V. (Science and Transport Progress, 2008)
The procedure allowing to determine the optimum values of main external parameters of a locomotive for driving trains with the given train set and technical speed of motion is presented.